Intravenous Injection of PHF-Tau Proteins From Alzheimer Brain Exacerbates Neuroinflammation, Amyloid Beta, and Tau Pathologies in 5XFAD Transgenic Mice - Houben, Sarah; de Fisenne, Marie-Ange; Ando, Kunie; Vanden Dries, Virginie; Poncelet, Luc; Yilmaz, Zehra; Mansour, Salwa; De Decker, Robert; Brion, Jean-Pierre; Leroy, Karelle (Frontiers in Molecular Neuroscience, 2020)
Alzheimer’s disease (AD) is characterized by the accumulation in the brain of intraneuronal aggregates of abnormally and hyperphosphorylated tau proteins and of extracellular deposits of amyloid-ß surrounded by dystrophic neurites. Numerous experimental models have shown that tau pathology develops in the brain after intracerebral injection of brain homogenates or pathological tau (PHF-tau) from AD brains. Further investigations are however necessary to identify or exclude potential extracerebral routes of tau pathology transmission, e.g. through the intravascular route. In this study, we have analysed the effect of intravenous injection of PHF-tau proteins from AD brains on the formation of tau and amyloid pathologies in the brain of wild-type mice and of 5XFAD mice (an amyloid model). We observed that 5XFAD mice with a disrupted blood brain barrier showed increased plaque-associated astrogliosis, microgliosis, and increased deposits of Aß40 and Aß42 after intravenous injection of PHF-tau proteins. In addition, an increased phosphotau immunoreactivity was observed in plaque-associated dystrophic neurites. These results suggest that blood products contaminated by PHF-tau proteins could potentially induce an exacerbation of neuroinflammation and AD pathologies.